Research on gating alignment strategy for flow scheduling in satellite formation - XU Chuan; ZHANG Rufeng; HE Xiongwen; CUI Zhaojing; ZHAO Guofeng (Tongxin xuebao)
Aiming at the time-sensitive network (TSN) gating scheduling required high synchronization accuracy of adjacent nodes, the delay fluctuation of inter-satellite wireless links caused the deviation of gate opening of adjacent nodes, resulting in the problem of inconsistent flow scheduling, a gating alignment strategy for flow scheduling in satellite formation was proposed. Firstly, the factors that affect the gating scheduling in satellite formation were analyzed, and the scheduling time constraints of traffic flow at switch ports were modeled to establish a gating on/off list model. Secondly, an online rolling gray scale prediction algorithm was designed to predict the delay of inter-node links, and based on the prediction results, the gated list deviation of neighboring nodes could be corrected dynamically to ensure the consistency of multi-node gated scheduling. Finally, the satellite formation software simulation scenario was established based on STK and EXata, moreover, the gating alignment strategy also was implemented on field programmable gate array (FPGA) hardware platform. The experimental results demonstrate that the proposed strategy can ensure that after 5-hops satellite transmission, the time delay of the time-sensitive traffic flow keeps on 3 782~3 848 μs, and the jitter is stable at 30 μs, which is 20% lower than the existing schemes.